2022
DOI: 10.1029/2021ea002032
|View full text |Cite
|
Sign up to set email alerts
|

The First Characterization of Fog Microphysics in the United Arab Emirates, an Arid Region on the Arabian Peninsula

Abstract: Fog occurs when condensation processes in the atmosphere allow for cloud droplet formation near the Earth's surface causing visibility to drop below 1 km (World Meteorological Organization, 2008). Fog has a major impact on society, most notably on the functioning of transportation networks, as the low visibility can result in delays or create hazardous conditions. Different fog types have been described in the literature and are essentially categorized based on the source of moisture and the mechanism through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It can be used to obtain information on N c , LWC, and visibility. This instrument is widely used to measure fog, allowing a consistent comparison of the results with those obtained in other studies (e.g., Weston et al, 2022;Gultepe et al, 2021;Mazoyer et al, 2019;Degefie et al, 2015;Gultepe et al, 2009).…”
Section: Introductionmentioning
confidence: 67%
“…It can be used to obtain information on N c , LWC, and visibility. This instrument is widely used to measure fog, allowing a consistent comparison of the results with those obtained in other studies (e.g., Weston et al, 2022;Gultepe et al, 2021;Mazoyer et al, 2019;Degefie et al, 2015;Gultepe et al, 2009).…”
Section: Introductionmentioning
confidence: 67%
“…This observation is expected, as the SHAMS location is further inland compared to other coastal locations, such as Barakah and Abu Dhabi. Previous studies conducted at Barakah reported the persistent occurrence of strong northwesterly winds for several days when the location is under the influence of favorable synoptic conditions (Abida et al, 2022;Nelli et al, 2022;Weston et al, 2022).…”
Section: Background Weather Conditions During Wise-uae Phase-1mentioning
confidence: 97%
“…Fog also developed in the early hours of 17 February (Figure 3 of Weston et al, 2022) but did not last as long, probably because of the rapid changes in the strength of the wind with speeds as high as 3.5 m s −1 and a prevailing onshore (north to northeast) direction. The microphysics of the fog events that occurred during this field campaign are reported in Weston et al (2022).…”
Section: Fog Event On 15-16 February 2021mentioning
confidence: 99%